Imaginary of Science - Martínez, Luciana (Universidad Nacional del Litoral, 2018)
Throughout the history of literature it is common to find testimony to the presence of imaginaries freely articulated around pre-modern scientific knowledge. The emergence of modern science, however, brought about greater complexity to the relations between literature and science. Newton’s mechanistic model —which had become dominant since then—, as well as the demands for verifiability and the separation of disciplines signalled the divorce between literature and science as to see mingle irreconcilable symbolic orders, whose ties bore strong institutional preconceptions. Nevertheless, literature has historically fictionalized science issues without prejudices. This exercise deploys operations for the appropriation and absorption of theories, resources and paradigms, always based on the creative logics and the interests of writing itself.